2000
DOI: 10.1097/00005537-200012000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Microvessel Density, the Expression of Vascular Endothelial Growth Factor (VEGF), and the Extension of Nasopharyngeal Carcinoma

Abstract: The metastatic potency of NPC tissue and the prognosis of the patients with NPC can be estimated by measuring MVD and the expression of VEGF in NPC tissue. Drugs that have inhibitory actions on angiogenesis could be useful to prevent metastasis of NPC cells in the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 23 publications
7
59
0
2
Order By: Relevance
“…[35][36][37] Furthermore, VEGF expression was found to be markedly increased and correlated with microvessel density in nasopharyngeal carcinoma patients. 30 Similarly, we herein found that TNFAIP2 is a downstream target of TNFa that acts as a potential angiogenic factor, as shown by the association of its expression with microvessel density in vivo.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…[35][36][37] Furthermore, VEGF expression was found to be markedly increased and correlated with microvessel density in nasopharyngeal carcinoma patients. 30 Similarly, we herein found that TNFAIP2 is a downstream target of TNFa that acts as a potential angiogenic factor, as shown by the association of its expression with microvessel density in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…Finally, we tested for a potential interaction between TNFAIP2 and VEGF, an important secreted angiogenesis-initiating factor that has also been correlated with microvessel density in nasopharyngeal carcinoma patients. 30 As the protein sequence of TNFAIP2 (amino acids 91-651) is highly similar to that of SEC6 (based on a publicly available website http://www.sanger.ac.uk/), an exocyst complex component involved in exocytosis 31 and secretion, 32 we examined whether TNFAIP2 affected the secretion of VEGF by HK1 cells. As shown in Figure 3d, our results revealed that VEGF secretion by HK1 cells was not affected by TNFAIP2 knockdown.…”
Section: Promotion Of Cell Migration and Invasion By Tnfaip2mentioning
confidence: 99%
“…VEGF is a key angiogenic stimulator, and its expression can directly induce angiogenesis. It is a prognostic factor and is highly expressed in metastatic cancers, including NPC (22,23). IL-8 is proangiogenic (24) and contributes to a poor prognosis in primary NPC (25).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor MVD is a significant and independent prognostic indicator for relapse-free and overall survival of cancer patients [152]. Similarly, elevated tumor or serum levels of the pro-angiogenic factors VEGF-A, interleukin (IL) and FGF-2 as well as a low ratio between the angiogenesis inhibitor thrombospondin-2 and VEGF-A are associated with an increased incidence of metastasis in cancer patients [153][154][155]. Xenograft animal models confirm the correlation of tumoral overexpression of angiogenic growth factors, increased MVD of primary and secondary tumors and metastasis formation [156][157][158].…”
Section: Tumor Angiogenesismentioning
confidence: 99%